A methodology to study high-speed pantograph-catenary interaction with realistic contact wire irregularities - Song, Yang (2020)
In high-speed rail operations, the irregularity of the overhead system is a typical disturbance that affects the pantograph-catenary interaction performance. The existing methods, which treat the contact wire irregularities as hard spots, overestimate the negative effect of the irregularities on the contact force, leading to conservative results. In this work, a more accurate methodology aiming to include the effect of contact wire irregularities in the assessment of the pantograph-catenary dynamic performance is proposed. Measured contact wire irregularity data, collected from the Chinese high-speed network, is added to the initial configuration of the catenary model, through a developed Target Configuration Under Dead-loads (TCUD) method. This approach is used here to investigate the effect of the contact wire irregularities on the contact forces. The results indicate that the catenary imperfections have a direct impact on the pantograph-catenary interaction, leading to an increment of the contact forces amplitude, an increase of their standard deviation and an expansion of the contact forces range. A frequency analysis of the results shows that the contact wire irregularity increases the Power Spectral Density (PSD) peaks of the contact force at specific frequencies relevant to the span length and to the dropper spacing.